2023
DOI: 10.17309/tmfv.2023.4.14
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between U21 and U23 Semi-Professional Soccer Players in Perfectionism and Passion

Ricardo Martín-Moya,
Adelaida Irene Ogallar-Blanco,
Eduardo García-Mármol
et al.

Abstract: Study purpose. The aim of this study is to analyse differences in perfectionism and passion and how these variables interact and might be expected to affect performance in U21 and U23 soccer players. Materials and methods. A total of 60 healthy semi-professional soccer players (age: 21.57±1.95 years; height: 179.76±5.79 cm) participated in the study. The participants were divided into two equal groups, one with those players younger than 21 years old and the other including players aged 21–23. This study was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Regarding differences between U23 and older players, t -test and Cohen’s d , showed some interesting results, as they revealed that U23 players showed significative differences in global perfectionism and concern over mistakes, the main subdimension of negative perfectionism. In this sense, further studies we conducted comparing levels of perfectionism among the U-23 soccer players of this sample ( Martín-Moya et al, 2023 ) also found that youngest players showed a higher level of negative perfectionism than their older, yet U-23 companions, suggesting that perfectionism is higher among the youngest. As aforementioned, concern over mistakes constitutes the apprehension about making mistakes and about the possible negative consequences these faults could entail.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Regarding differences between U23 and older players, t -test and Cohen’s d , showed some interesting results, as they revealed that U23 players showed significative differences in global perfectionism and concern over mistakes, the main subdimension of negative perfectionism. In this sense, further studies we conducted comparing levels of perfectionism among the U-23 soccer players of this sample ( Martín-Moya et al, 2023 ) also found that youngest players showed a higher level of negative perfectionism than their older, yet U-23 companions, suggesting that perfectionism is higher among the youngest. As aforementioned, concern over mistakes constitutes the apprehension about making mistakes and about the possible negative consequences these faults could entail.…”
Section: Discussionmentioning
confidence: 59%
“…A subsample derived from this main sample, comprising only U23 players, has been used in subsequent studies belonging to the same project derived from these findings ( Martín-Moya et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%